2020
DOI: 10.1016/j.annonc.2020.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Genomic origin and EGFR-TKI treatments of pulmonary adenosquamous carcinoma

Abstract: Background: Adenosquamous carcinoma (ASC) of the lung is a heterogeneous disease that is composed of both adenocarcinoma components (ACC) and squamous cell carcinoma components (SCCC). Their genomic profile, genetic origin, and clinical management remain controversial. Patients and methods: Resected ASC and metastatic tumor in regional lymph nodes (LNs) were collected. The ACC and SCCC were separated by microdissection of primary tumor. The 1021 cancer-related genes were evaluated by nextgeneration sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 32 publications
7
61
1
Order By: Relevance
“…Most mutated cancer genes were known as typical for LUAD such as EGFR, MET and BRAF. P118 harbored a deletion in EGFR exon 19, a well-known driver gene in LUAD [6,22]. We found only KMT2D in P120, but not any other mutations in LUSC typical driver genes (Fig.…”
Section: Evolutionary History Of Genetic Alterationsmentioning
confidence: 60%
See 3 more Smart Citations
“…Most mutated cancer genes were known as typical for LUAD such as EGFR, MET and BRAF. P118 harbored a deletion in EGFR exon 19, a well-known driver gene in LUAD [6,22]. We found only KMT2D in P120, but not any other mutations in LUSC typical driver genes (Fig.…”
Section: Evolutionary History Of Genetic Alterationsmentioning
confidence: 60%
“…Previous studies focusing on oncogenic driver mutations revealed that ASC have similar mutation profiles and therapeutic targets as LUAD including EGFR mutations [5,6]. Yet, to the best of our knowledge, the genomic profiles of the LUAD and LUSC components within ASC and the inferred evolutionary trajectories have not been explored previously, beyond the use of single gene and gene panel testing [5,6]. Being defined by its distinct morphological heterogeneity, ASC represents an ideal model to study morphological transdifferentiation and clonal evolution in NSCLC.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…And we hypothesized that AC-predominant ASC might be in a later, better-differentiated phase in this transition and thus be with a better prognosis. However, recent data suggested that Asian pulmonary ASC might originate from adenocarcinoma and that squamous cell carcinoma components might be transformed from adenocarcinoma components [19]. Thus, further research is needed to explore this issue.…”
Section: Discussionmentioning
confidence: 99%